The Effect of Ad Exposure on Consumer Visual Attentions Depending on Time Lapse in the Context of eSports - Byung-Jae Min; Daehwan Kim (Korea Institute of Sport Science, 2023)
PURPOSE This study examined how consumers' visual attention to ads during eSports media consumption varies over time. METHODS An experimental study with a single factor, three-level within subject experimental design was conducted, utilizing an eye-tracker to measure visual attentions, including fixation count and duration. Seventy-eight students from a national university in city B participated in the experiment. A repeated measures ANOVA was conducted using the open-source statistical program R to test the research hypothesis. RESULTS Both the fixation count and duration were highest for the first ad and then gradually decreased for the second and third ad. CONCLUSIONS It is recommended that eSports sponsors should consider differentiating ad pricing based on the order of exposure, then expose the first ad presented more frequently and for extended periods, and consider different shapes, colors, and movements to prevent adaptation to the initial allocation of attention.